Socialised Shopper: An empirical study of shoppers’ browsing psychology, social media and share to purchase behavior - Singh, Samarth; Maitri (International Journal of Psychosocial Rehabilitation, 2020)
As Indian economy is moving towards digitalization there would be more digital shopper- retailer interactions like social media interactions etc. Recognizing the importance of social media during shoppers purchase journey and their browsing psychology in a retail outlet, this paper reports results from an empirical study that investigates shoppers browsing psychology and social media behavior undertaken in organized retail in Delhi. It studies shopper’s social media behavior on retailer’s social pages along with the share to purchase behavior so as to understand the usefulness of such interactions. Further it studies shoppers browsing psychology in terms of usage of shopping list, on pack information and browsing of aisles. Five hundred shoppers’ data was attained using a survey questionnaire. Study reveals that majority of the shoppers visit retailer’s social pages to avail exclusive discount followed by socializing with friends to know more about products they want to buy, to participate in competitions, to earn rewards points, to provide product feedback, to avail after sales services and to launch complaints. Further, highlighting the share to purchase behavior it reveals that thirty eight percent (five percent of total shoppers) of those who went to the retailer’s site through sharing on social media have purchased the product from physical store. Regarding browsing psychology only 19 percent shoppers frequently use shopping list,22 percent shoppers look for on pack information and go to intended isle directly and majority of shoppers go for assistance to sales staff Research outcomes encourage retailers to implement technology driven targeted marketing.